Effect of the REG1 anticoagulation system versus bivalirudin on outcomes after percutaneous coronary intervention (REGULATE-PCI): a randomised clinical trial. Issue 10016 (23rd January 2016) - Lincoff, A Michael; Mehran, Roxana; Povsic, Thomas J; Zelenkofske, Steven L; Huang, Zhen; Armstrong, Paul W; Steg, P Gabriel; Bode, Christoph; Cohen, Mauricio G; Buller, Christopher; Laanmets, Peep; Valgimigli, Marco; et al.
Summary: Background: REG1 is a novel anticoagulation system consisting of pegnivacogin, an RNA aptamer inhibitor of coagulation factor IXa, and anivamersen, a complementary sequence reversal oligonucleotide. We tested the hypothesis that near complete inhibition of factor IXa with pegnivacogin during percutaneous coronary intervention, followed by partial reversal with anivamersen, would reduce ischaemic events compared with bivalirudin, without increasing bleeding. Methods: We did a randomised, open-label, active-controlled, multicentre, superiority trial to compare REG1 with bivalirudin at 225 hospitals in North America and Europe. We planned to randomly allocate 13 200 patients undergoing percutaneous coronary intervention in a 1:1 ratio to either REG1 (pegnivacogin 1 mg/kg bolus [>99% factor IXa inhibition] followed by 80% reversal with anivamersen after percutaneous coronary intervention) or bivalirudin. Exclusion criteria included ST segment elevation myocardial infarction within 48 h. The primary efficacy endpoint was the composite of all-cause death, myocardial infarction, stroke, and unplanned target lesion revascularisation by day 3 after randomisation. The principal safety endpoint was major bleeding. Analysis was by intention to treat. This trial is registered at ClinicalTrials.gov, identifier NCT01848106 . The trial was terminated early after enrolment of 3232 patients due to severe allergic reactions. Findings: 1616 patients were allocated REG1 and 1616 were assigned bivalirudin, of whom 1605 and 1601 patients, respectively, received the assigned treatment. Severe allergic reactions were reported in ten (1%) of 1605 patients receiving REG1 versus one (<1%) of 1601 patients treated with bivalirudin. The composite primary endpoint did not differ between groups, with 108 (7%) of 1616 patients assigned REG1 and 103 (6%) of 1616 allocated bivalirudin reporting a primary endpoint event (odds ratio [OR] 1·05, 95% CI 0·80–1·39; p=0·72). Major bleeding was similar between treatment groups (seven [<1%] of 1605 receiving REG1 vs two [<1%] of 1601 treated with bivalirudin; OR 3·49, 95% CI 0·73–16·82; p=0·10), but major or minor bleeding was increased with REG1 (104 [6%] vs 65 [4%]; 1·64, 1·19–2·25; p=0·002). Interpretation: The reversible factor IXa inhibitor REG1, as currently formulated, is associated with severe allergic reactions. Although statistical power was limited because of early termination, there was no evidence that REG1 reduced ischaemic events or bleeding compared with bivalirudin. Funding: Regado Biosciences Inc.